TINJAUAN YURIDIS PUTUSAN HAKIM NOMOR 26/Pid.Sus.Anak/2021/PNSak TINDAK PIDANA NARKOTIKA DENGAN PELAKU ANAK SEBAGAI PERANTARA: Narkotika; Anak; Analisis Putusan - Assalavia, Vilova (NOVUM : JURNAL HUKUM, 2014)
The judge's decision is the final decision taken by the judge in the trial to determine whether the defendant will be sentenced or not. This decision is an official statement from the judge in resolving a case in court and has permanent legal force. This decision serves as a legal basis that determines the rights, obligations, or sanctions that must be carried out by the parties involved in the case. Independent judicial power is used to uphold law and justice. In Decision Number 26/Pid.Sus.Anak/2021/PNSak, the child was ordered by his biological brother to store methamphetamine. This research is conducted to examine and analyze whether the judge has considered the sociological factors of the defendant and analyze how the influence of the judge's consideration of the defendant's sociological factors on the imposition of punishment in Decision Number 26/Pid.Sus.Anak/2021/PNSak. This research is useful for reviewing and analyzing legal norms, as well as the judge's decision using normative legal research. The approaches used include statute approach, case approach and concept approach. This analysis also uses prescriptive. The results of this study are the Decision of the Judge of the Siak Indrapura District Court in case Number 26/Pid.Sus.Anak/2021/PNSak, which has fulfilled the juridical elements but the judge did not pay enough attention to the sociological aspects of the defendant because it did not cover the defendant's condition at that time. The child followed his brother's orders to store methamphetamine due to threats from him.